2021
DOI: 10.1088/1361-6560/abcbcf
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a CT-based motion model with in-situ fluoroscopy for lung surface deformation estimation

Abstract: Many surrogate-based motion models (SMMs), proposed to guide motion management in radiotherapy, are constructed by correlating motion of an external surrogate and internal anatomy during CT-simulation. Changes in this correlation define model break down. We validate a methodology that incorporates fluoroscopic images (FL) acquired during treatment for SMM construction and update. Under a prospective IRB, 4DCT scans, VisionRT 25 surfaces, and orthogonal FLs were collected from five lung cancer patients. VisionR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…In that report, the NMI between 2D X-ray images and DRRs was shown to be 0.45-0.85 in five lung patients. Our analysis of nine lung patients showed that the NMI was 0.43-0.71 in orthogonal images; these findings are in agreement with [23]. Using the proposed CEF method, the NMI was 0.57-0.80 in lung patients.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In that report, the NMI between 2D X-ray images and DRRs was shown to be 0.45-0.85 in five lung patients. Our analysis of nine lung patients showed that the NMI was 0.43-0.71 in orthogonal images; these findings are in agreement with [23]. Using the proposed CEF method, the NMI was 0.57-0.80 in lung patients.…”
Section: Discussionsupporting
confidence: 88%
“…The similarity between DRRs and 2D X-ray images was evaluated using NMI. Ranjbar et al, [23] assessed the similarity between fluoroscopic images and DRRs created from 4DCT using NMI. In that report, the NMI between 2D X-ray images and DRRs was shown to be 0.45-0.85 in five lung patients.…”
Section: Discussionmentioning
confidence: 99%
“…higher dimensional) conditioning if available. For instance, more complex respiratory patterns could be better captured through clinically available real-time entire external surface measurements by optical devices (Nazir et al 2018, Ranjbar et al 2021. Including such information in the conditioning may thus further improve the model performance, which we will investigate in future research.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Periodic motions, such as those caused by breathing or heart-beat,has been a topic of lively research over the last 20 years. [15][16][17][18][19] Typically, such approaches use models, for instance surrogate motion models, to estimate motion that is otherwise not directly accessible, 19,20 instead of real yet inaccessible organ motion, for example, lung deformation estimated from the thoracoabdominal surface 19 or by measuring air flow changes by spirometry. 21,22 Inherent errors from such surrogates lie in potential miscorrelation with the internal organ motion they shall represent.…”
Section: Introductionmentioning
confidence: 99%